Tea economy: special reference from Kerala - S. Vidya (Indian Journal of Economics and Development, 2018)
Objectives: To analyse the trends and pattern of area, production and yield of tea plantation in Kerala and to study the problems and prospects of small and marginal farmers engaged in tea cultivation and sustainability of tea plantations in Wayanad District. Methods/Statistical Analysis: Investigation is based on both primary and secondary data. The trends and pattern of area, production and yield of tea plantation Kerala and in India as a whole and studied using secondary sources like the publications of Tea board, United Planters Association of Southern India, Agricultural Statistics, Economic Review, Indian Economic Journal, Economic and Political Weekly and also web sites. The primary survey conducted in Vythiri Panchayat in Wayanad district one of the hilly districts in Kerala. A sample of 100 marginal farmers was taken for this study. Findings: Till 2005, India was the largest tea producer in the world, but after 2005 China takes the position. Production of tea in India declined because of many reasons like price fluctuations, changes of climatic conditions, Economic crisis etc. Production of tea in Kerala and in Wayanad also declined, but now lots of small and marginal farmers came in to tea cultivation because, compared to other plantation crops like pepper, coffee, cardamom etc., the number of yield is high. That is in between three months the growers collect the tea leaves. Therefore, the major attracting factor for the new growers was the profit maximisation. Applications/Improvements: State and local government initiatives were necessary for the better production tea in small and marginal farmers. Like other plantation crops, subsidies are necessary for more productive and profitable and it helps to change the standard living of the farmers.